TGF-β phospho antibody array identifies altered SMAD2, PI3K/AKT/SMAD, and RAC signaling contribute to the pathogenesis of myxomatous mitral valve disease - McNair, Andrew J.; Markby, Greg R.; Tang, Qiyu; MacRae, Vicky E.; Corcoran, Brendan M. (Frontiers in Veterinary Science, 2023)
Background TGFβ signalling appears to contribute to the pathogenesis of myxomatous mitral valve disease (MMVD) in both the dog and human. However, little is known about the extent of the downstream signalling changes that will then affect cell phenotype and function in both species. Objective Identify changes in downstream signals in the TGFβ pathway in canine MMVD and examine the effects of antagonism of one significant signal (SMAD2 was selected). Materials and Methods Canine cultures of normal quiescent valve interstitial cells (qVICs) and disease derived activated myofibroblasts (aVICs) (n=6) were examined for TGFβ signalling protein expression using a commercial antibody array. Significant changes were confirmed, and additional proteins of interest in the TGFβ signalling pathway and markers of cell phenotype were examined (PRAS40, S6K, elF4E IRS-1, αSMA, VIM), using protein immunoblotting. RT-PCR examined expression of gene markers of VIC activation (ACTA2, TAGLN, MYH10; encoding the proteins αSMA, SM22 and Smemb respectively). Attenuation of pSMAD2 in aVICs was examined using a combination of RNA interference technology (siRNA) and the SMAD7 (antagonises SMAD2) agonist asiaticoside.The antibody array identified significant changes (P<0.05) in 19 proteins of which 6 were phosphorylated (p). There was increased expression of pSMAD2, pRAC1 and decreased expression of pmTOR, pERK1/2 and pAKT1. Expression of pPRAS40 and pIRS-1 was increased as was the mTOR downstream transcription factor pS6K, with increased expression of peIF4E in aVICs, indicating negative feedback control of the PI3K/AKT/mTOR pathway. SMAD2 antagonism by siRNA and the SMAD7 agonist asiaticoside decreased detection of pSMAD by at least 50%, significantly decreased expression of the aVIC gene markers ACTA2, TAGLN and MYH10, and pαSMA, pAKT2 and pERK1, but had no effect on pS6K, pERK2 or pVIM expression in aVICs. SMAD2 antagonism transitioned diseased aVICs to normal qVICs, while maintaining a mesenchymal phenotype (VIM+) and concurrently affecting non-canonical TGFβ signalling. Conclusion MMVD is associated with changes in both the canonical and non-canonical TGFβ signalling pathway. Antagonism of SMAD2 transitions diseased activated myofibroblasts back to a normal phenotype, providing data that will inform studies on developing novel therapeutics to treat MMVD in the dog and human.